GCG structure’s and disclosure to investors’ impacts on ROE in non-bank financing sector companies - Nova Tri Anggraini; Rusdiah Iskandar; Wirasmi Wardhani (Interdisciplinary Social Studies, 2024)
This study aims to determine the effect of Shareholders' Rights and the Board of Directors as well as the Audit Committee and Disclosure to Investors on Return On Equity in Financing Companies listed on the Indonesia Stock Exchange (Period 2018-2022). Through this quantitative approach, the research method used is descriptive analysis and hypothesis testing with a total population of 20 non-bank financing companies and a sample of 4 non-bank financing companies listed during the 2018-2022 period. The results show that Shareholders' Rights and the Audit Committee have a significant effect on ROE. In contrast, the Board of Directors and Disclosure to Investors show no effect on ROE.